The Impact of Inflation, BI Rate, and IDR/USD Exchange Rates on the Indonesian Stock Market: Time-Series Evidence from Indonesia (2020-2024) - Safira Arindia Putri; Jojok Dwiridotjahjono (FEBI IAIN Langsa, 2026)
This study addresses this gap by investigating the impact of inflation, the BI Rate, and the IDR/USD exchange rate on the Indonesian Composite Stock Price Index (IHSG) over the disruptive 2020-2024 period, encompassing the COVID-19 pandemic and subsequent economic rebound. While the influence of macroeconomic variables on stock markets is well-documented, studies specifically examining the behavior of the inflation, the central bank policy rate, and the IDR/USD exchange rate during a post-crisis recovery period in Indonesia remain scarce. This study employing a quantitative associative design, this research analyzes monthly secondary data (n=60) using multiple linear regression in SPSS, following classical assumption tests. The findings reveal a significant simultaneous effect of these three variables on the IHSG, confirming their collective contribution to market fluctuations. Partially, however, only inflation exhibits a statistically significant positive relationship. This finding is intriguing as it appears to contradict the conventional Fisher Effect, which typically frames inflation as a negative signal. In the specific context of a post-pandemic economic resurgence, this positive inflation may have been interpreted by market participants as a sign of strengthening aggregate demand and accelerating growth, rather than purely a monetary risk indicator. Conversely, the BI Rate and exchange rate show no significant individual effects. The model’s R² of 0.312 indicates that 31.2% of IHSG variation is explained by these factors. This research contributes theoretically by providing empirical evidence of an inflation anomaly in an emerging market recovering from crisis, and offers practical insights for policymakers and investors in interpreting macroeconomic signals.